Hubungan Berat Badan dengan Kualitas Tidur pada Mahasiswa Fakultas Kedokteran dan Ilmu Kesehatan, Universitas Kristen Krida Wacana Angkatan 2016 - Mohamad Naim Bin Hasan; William William; Flora Rumiati (Fakultas Kedokteran Universitas Kristen Krida Wacana, 2020)
Overweight is an independent factor that contributes to poor sleep quality. Sleep apnea is abnormal breathing associated with constriction of the upper airway during sleep. Sleep apnea can be in the form of apnea or decreased ventilation leading to breathing problems during sleep. The higher the value of the Body Mass Index (BMI) or weight gain, the higher the possibility to experience Obstructive Sleep Apnea (OSA). The purpose of this study was to determine the relationship between BMI and sleep quality among medical students of Ukrida from class of 2016. The study was based on a cross sectional approach and subjects were determined based on a purposive sampling technique. Eighty-eight medical students of Ukrida from 2016 intake completed the Pittsburgh Sleep Quality Index assessment. Chi-Square test was used to analyze the relationship between BMI with sleep quality in overweight and normal weight students. Forty-four respondents were of normal weight, whereas 44 were overweight. Results showed 64 respondents (72.7%) had poor sleep quality, and 24 respondents (27.3%) had good sleep quality. Most of the respondents had sleep duration of <6 hours. Chi square analysis found that BMI was related with sleep quality (p = 0.000, p < 0.05) among the students participated in this study.